Alteration in forward model prediction of sensory outcome of motor action in focal hand dystonia - Lee, André; Furuya, Shinichi; Karst, Matthias; Altenmüller, Eckart (Frontiers in Human Neuroscience, 2013)
Focal hand dystonia in musicians is a movement disorder affecting highly trained movements. Rather than being a pure motor disorder related to movement execution only, movement planning, error prediction and sensorimotor integration are also impaired. Internal models, of which two types, forward and inverse models have been described and most likely processed in the cerebellum, are known to be involved in these tasks. Recent results indicate that the cerebellum may be involved in the pathophysiology of focal dystonia. Thus the aim of our study was to investigate whether an internal model deficit plays a role in focal dystonia. We focused on the forward model, which predicts sensory consequences of motor commands and allows the discrimination between external sensory input and input deriving from motor action. We investigated 19 patients, aged 19-59 and 19 healthy musicians aged 19-36 as controls. Tactile stimuli were applied to fingers II–V of both hands by the experimenter or the patient. After each stimulus the participant rated the stimulus-intensity on a scale between 0 (no sensation) and 1 (maximal intensity). The difference of perceived intensity between self- & externally applied stimuli was then calculated for each finger. For assessing differences between patients and controls we performed a cluster analysis of the affected hand and the corresponding hand of the controls using the fingers II–V as variables in a 4-dimensional hyperspace (chance level=0.5). Using a cluster analysis, we found a correct classification of the affected finger in 78,9%-94.7%. There was no difference between patients and healthy controls of the absolute value of the perceived stimulus intensity. Our results suggest an altered forward model function in focal hand dystonia. It has the potential of suggesting a neural correlate within the cerebellum and of helping integrate findings with regard to altered sensorimotor processing and altered prediction in FD in a single framework.